Diabetes converts arterial regulation by perivascular adipose tissue from relaxation into H(2)O(2)-mediated contraction - Emilova, R; Dimitrova, D Z; Mladenov, M; Hadzi-Petrushev, N; Daneva, T; Padeshki, P; Schubert, R; Chichova, M; Lubomirov, L; Simeonovska-Nikolova, D; Gagov, H (Physiological research, 2016)
This study aims to reveal the reason for the increased force of 5-hydroxytryptamine-induced contraction of endothelium-denuded skeletal muscle arteries of diabetic rats in the presence of perivascular adipose tissue (PVAT). Our data on rat gracilis arteries show that i) PVAT of skeletal muscle arteries of healthy and diabetic rats releases hydrogen peroxide (H(2)O(2)), ii) higher concentrations of 5-hydroxytryptamine increase the production of H(2)O(2) in PVAT; iii) an enhanced PVAT production of H(2)O(2) is the main, if not the only, reason for the sensitization of arterial contraction to 5-hydroxytriptamine-induced contraction in diabetes and iv) endothelium antagonizes the effect of PVAT-derived H(2)O(2).
Keywords: Hydrogen Peroxide; experimentální diabetes mellitus; Arteries; vazokonstrikce; zvířata; tuková tkáň; serotonin; Adipose Tissue; peroxid vodíku; mužské pohlaví; Diabetes Mellitus, Experimental; Serotonin; Vasoconstriction; Rats, Wistar; potkani Wistar; Animals; arterie; kosterní svaly; Muscle, Skeletal; Male